Microfluidic-based models to address the bone marrow metastatic niche complexity. (April 2021) - Ribeiro, Patrícia; Leitão, Luís; Monteiro, Ana C.; Bortolin, Andrea; Moura, Beatriz; Lamghari, Meriem; Neto, Estrela
Abstract: Bone marrow (BM) is a preferential metastatic site for solid cancers, contributing to higher morbidity and mortality among millions of oncologic patients worldwide. There are no current efficient therapies to minimize this health burden. Microfluidic based in vitro models emerge as powerful alternatives to animal testing, as well as promising tools for the development of personalized medicine solutions. The complexity associated with the BM metastatic niche originated a wide variety of microfluidic platforms designed to mimic this microenvironment. This review gathers the essential parameters to design an accurate in vitro microfluidic device, based on a comparative analysis of existing models created to address the different steps of the metastatic cascade.